Quantitative matching of CO2 amounts via seismic attributes in the Sleipner field - Cheong, Snons; Yelisetti, Subbarao; Sanchez, Veronica (Frontiers in Earth Science, 2025)
The Sleipner field in the North Sea has been a cornerstone in the study of aquifer CO2 sequestration, with over 20 years of monitoring through time-lapse seismic analysis. This world-class project has provided critical insights into CO2 storage by detecting anomalous events in seismic imagery, confirming CO2 migration and stabilization within the subsurface. The study observed the growth of the CO2 plume within the storage aquifer layer by analyzing the seismic amplitude differences between baseline and subsequent monitoring data. The availability of precise seismic datasets in the Sleipner Project has not only facilitated monitoring validation but also spurred further research into CO2 quantification. This study focused on verifying the correlation between the amounts of stored CO2 and seismic attributes. Reflection data previously acquired revealed seismic anomalies attributed to the subsurface CO2 plume. The trace envelope attribute, which only registers positive values, was found to be particularly effective in delineating the primary boundary of the CO2-affected region. To advance quantitative monitoring, a new CO2 indicator attribute was developed, derived from the trace envelope and similarity variance. The application of this attribute resulted in an improvement in regression estimation accuracy, increasing from 0.9895 to 0.9906. The successful matching of CO2 storage data with seismic attributes demonstrates that fluid substitution can be quantitatively assessed using seismic data manipulation over time, underscoring the potential of seismic analysis for accurate CO2 monitoring in subsurface storage projects.